2019
DOI: 10.1186/s12967-019-2002-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel method for simultaneously detecting HPA and HLA antibodies using Luminex microbeads

Abstract: Background Alloantibodies against human platelet antigens (HPAs) and human leukocyte antigen (HLA) are implicated in several immune-mediated platelet disorders. Detection of these antibodies is crucial in the diagnosis and management of these disorders. The aim of this study was to establish a novel method to simultaneously detect HPA-1, HPA-2, HPA-3, HPA-5 and HLA antibodies with Luminex microbeads technology. Methods Monoclonal antibodies specific for platelet glycopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Therefore, platelet serology is in constant development and we agree with Porcelijn et al, 2020 9 that there is variation in antigen recognition and that some challenging clinical issues need more than one assay. One example of this are the rare HPAs in the Chinese population for which beads could not cover the antibody detection 16 and it is crucial also for a mixed population, such as the Brazilian.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, platelet serology is in constant development and we agree with Porcelijn et al, 2020 9 that there is variation in antigen recognition and that some challenging clinical issues need more than one assay. One example of this are the rare HPAs in the Chinese population for which beads could not cover the antibody detection 16 and it is crucial also for a mixed population, such as the Brazilian.…”
Section: Discussionmentioning
confidence: 99%
“…When tested for the presence of anti-HPA-1, anti-HPA-2, anti-HPA-3, anti-HPA-5 and anti-HLA in 44 clinical samples, the results of the Luminex technology were in agreement with the MAIPA. Interestingly, the Luminex technology failed at detecting anti-HPA-15, until lately [10,11], thus further confirming that detection of anti-HPA-15 is challenging, likely as a result of the generally low and variable antigen expression level [12,13]. However, M€ ortberg et al (2016) found that the modified monoclonal antibody immobilization of platelet antigens assay (MAIPA) using biotinylated monoclonal antibodies, streptavidin-coated beads and detection by flow cytometry, allowed for improved HPA antibody detection with high sensitivity for all assessed antibodies (anti-HPA-1a, anti-HPA-3a, anti-HPA-5b and anti-HPA-15b).…”
Section: Discussionmentioning
confidence: 99%
“…They were able to optimize conditions to obtain good sensitivity, reproducibility and specificity. Tao and coworkers have used Luminex microbeads to simultaneously detect anti‐HPA‐1, anti‐HPA‐2, anti‐HPA‐3, anti‐HPA‐5 and anti‐HLA antibodies [10]. This assay shares similarities with the Pak Lx assay reported herein.…”
Section: Discussionmentioning
confidence: 99%